FSDT-Based Numerical Analysis of Functionally Graded Plate under Uniform and Sinusoidally Distributed Loading - Satyam Tiwari; Rajesh Kumar Satankar (International Journal of Scientific Research in Science and Technology, 2025)
The present study focuses on the linear static analysis of unidirectional functionally graded material plates using a numerical technique based on the First order Shear Deformation Theory within the commercially available software ANSYS. The FGM plates considered are composed of a mixture of Silicon Nitride as the ceramic phase and SUS304 as the metallic phase, and their stiffness properties are used to investigate the effect of various gradation patterns on centroidal deflection and axial normal stress under different boundary conditions. The plates are subjected to pressure, which is uniformly and sinusoidally distributed over the plate surface. Convergence and validation tests have been performed to demonstrate the accuracy and reliability of the results through comparison with existing literature. A parametric study of moderately thick FGM plates reveals that centroidal deflection is minimal for ceramic-rich plates and maximal for metal-rich plates. Additionally, the axial normal stress behaviour largely mirrors that of centroidal deflection, except in the case of metallic plates, indicating a degree of independence from the modulus of elasticity.
Keywords: FGM; FEM; FSDT; Static Analysis; ANSYS